Advance Care Planning interventions for older people with early-stage dementia: A scoping review. (June 2022) - Tetrault, Annika; Nyback, Maj-Helen; Vaartio-Rajalin, Heli; Fagerström, Lisbeth
Advance Care Planning can be used to engage people with dementia in decision-making about future care. The current study aims to advance the state of knowledge about Advance Care Planning interventions aimed at older people with early-stage dementia and to describe the effects of various interventions as well as the feedback on the interventions from this patient group and their family caregivers. The study is reported in accordance with PRISMA for scoping reviews. The search for studies and reports included electronic databases, websites, books, and reference lists. Data from the selected studies, including publication year, title, purpose, study population, intervention, methods, and results, were extracted. Six full-text articles were identified as suitable for inclusion. The six interventions had differing approaches. A supportive structure was helpful for both people with dementia and family caregivers. The feeling of being listened to and engaged in the care planning seems to be of most importance, not the intervention design itself.